2016
DOI: 10.1186/s13019-016-0526-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of a video-assisted thoracoscopic lobectomy program in a single institution: results before and after completion of the learning curve

Abstract: BackgroundThe development of a video assisted thoracic surgery lobectomy (VATS-L) program provides a dedicated surgical team with a recognized learning curve (LC) of 50 procedures. We analyse the results of our program, comparing the LC with subsequent cases.MethodsFrom June 2012 to March 2015, we performed n = 146 VATS major pulmonary resections: n = 50 (Group A: LC); n = 96 (Group B). Pre-operative mediastinal staging followed the National Comprehensive Cancer Network guidelines. All procedures were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…Almost 25% of patients had chemotherapy before surgery, but in this cohort, we included different cases that could be differently evaluated on the basis of the clinical experience of the recruiting centre. The initial doubts about VATS-L oncological adequacy for early-stage NSCLC have been overcome, as demonstrated by several authoritative papers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10); the minimally invasive technique and the traditional open technique have proven to be equivalent in terms of overall survival and disease free-survival also for locally advanced NSCLC (10)(11)(12)(13). Unfortunately, our study lacks of mid-and long-term survival results; however, we have some valid oncological data such as the extent of lymphadenectomy and the resection margin status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost 25% of patients had chemotherapy before surgery, but in this cohort, we included different cases that could be differently evaluated on the basis of the clinical experience of the recruiting centre. The initial doubts about VATS-L oncological adequacy for early-stage NSCLC have been overcome, as demonstrated by several authoritative papers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10); the minimally invasive technique and the traditional open technique have proven to be equivalent in terms of overall survival and disease free-survival also for locally advanced NSCLC (10)(11)(12)(13). Unfortunately, our study lacks of mid-and long-term survival results; however, we have some valid oncological data such as the extent of lymphadenectomy and the resection margin status.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, several and authoritative authors demonstrated the efficacy of VATS lobectomy in terms of oncological results and validity of mediastinal intra-operative staging (7)(8)(9)(10), but the use of VATS-L for locally advanced-stage NSCLC is not well established. Some preliminary and single-centre retrospective studies have shown that VATS-L is feasible, safe and effective with long-term oncologic outcomes comparable to lobectomy via thoracotomy (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of this study is its retrospective nature and that it was conducted in a single institute. As also indicated by Gonfiotti and colleagues, 22 several factors can affect the duration and efficacy of the learning curve period; the experience in other complex VATS procedures or in standard open major pulmonary resections; the selection of a dedicated surgical team; the opportunity to concentrate on the learning curve procedures within a short period; and finally, the development of a proctored and stepwise program. Although this study was divided by surgical level, the difficulty of the procedure differs, depending on anatomic variations among each level.…”
Section: Study Limitationsmentioning
confidence: 91%
“…Our study results indicate that the curricula of thoracic surgery fellowship programs which incorporate the use of minimally invasive surgery technique appear to be more important when compared to the years since the completion of fellowship for adoption of these methods. The learning curve for minimally invasive lobectomy has been reported to be 50 cases [ 6 , 10 ]. MIE generally has more steps involved and is a longer operation than a lobectomy, but has been increasingly used as an alternative to an open approach [ 9 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%